The Three Hundred project: the gas disruption of infalling objects in cluster environments. Issue 4 (7th January 2021) - Mostoghiu, Robert; Arthur, Jake; Pearce, Frazer R; Gray, Meghan; Knebe, Alexander; Cui, Weiguang; Welker, Charlotte; Cora, Sofía A; Murante, Giuseppe; Dolag, Klaus; Yepes, Gustavo
Abstract: We analyse the gas content evolution of infalling haloes in cluster environments from The Three Hundred project, a collection of 324 numerically modelled galaxy clusters. The haloes in our sample were selected within 5 R 200 of the main cluster halo at $z$  = 0 and have total halo mass M 200 ≥ 10 11 h −1 M⊙ . We track their main progenitors and study their gas evolution since their crossing into the infall region, which we define as 1–4 R 200 . Studying the radial trends of our populations using both the full phase-space information and a line-of-sight projection, we confirm the Arthur et al. (2019) result and identify a characteristic radius around 1.7 R 200 in 3D and at R 200 in projection at which infalling haloes lose nearly all of the gas prior their infall. Splitting the trends by subhalo status, we show that subhaloes residing in group-mass and low-mass host haloes in the infall region follow similar radial gas-loss trends as their hosts, whereas subhaloes of cluster-mass host haloes are stripped of their gas much further out. Our results show that infalling objects suffer significant gaseous disruption that correlates with time-since-infall, cluster-centric distance, and host mass, and that the gaseous disruption they experience is a combination of subhalo pre-processing and object gas depletion at a radius that behaves like an accretion shock.